2017
DOI: 10.5603/gp.a2017.0115
|View full text |Cite
|
Sign up to set email alerts
|

What influences women’s contraceptive choice? A cross-sectional study from Turkey

Abstract: Objectives: In our study, we tried to investigate the determinants of women's choices about contraception with the aim of discovering whether or not there is a difference in their preferences before and after consultation with a gynaecologist. Material and methods:A total of 1058 women were enrolled. They were given detailed information regarding contraception and contraceptive methods. Subsequently, a survey which was made of 21 questions was administered.Results: Contraceptive counselling significantly chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…A recent systematic review of patient preferences for contraceptive counselling found that women value comprehensive education about methods, with a emphasis on education about side effects [28,29]. Kahramanoglu et al [15] evaluated women's choices about contraception before and after gynecologist counselling. Physicians and health care providers were the best source for information about contraception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of patient preferences for contraceptive counselling found that women value comprehensive education about methods, with a emphasis on education about side effects [28,29]. Kahramanoglu et al [15] evaluated women's choices about contraception before and after gynecologist counselling. Physicians and health care providers were the best source for information about contraception.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to inadequate counselling given to women regarding modern contraception methods. Kahramanoglu et al evaluated the differences in contraceptive choices before and after counselling Turkish women and suggested that contraceptive counselling significantly changed the contraceptive choices of women [15]. However, few studies have been published on how to implement contraceptive counselling to women [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Sie gliedern sich in quantitative und qualitative Studien. In den sechs identifizierten quantitativen Studien mit Jugendlichen und jungen Erwachsenen wurde für unterschiedliche Länder wie Großbritannien (Whitfield et al 2013 ), die USA (Kofinas et al 2014 ; Sutton und Walsh-Buhi 2017 ; Stevens et al 2017 ), Nigeria (Bankole und Onasote 2017 ) und die Türkei (Kahramanoglu et al 2017 ) gezeigt, dass das Internet eine wichtige Quelle für Verhütungsinformationen ist. Die drei aufgefundenen qualitativen Studien gehen ergänzend genauer auf die Umstände der Nutzung ein.…”
Section: Forschungsstandunclassified
“…Further in our survey data on the education and social status of the participants are missing. These factors also influence the type of contraceptive methods and rate of regret [38][39][40] and should also be recorded in future surveys regarding this question.…”
Section: Fsfimentioning
confidence: 99%